Gifts in Croatian public and academic libraries - Hebrang Grgić, Ivana (2011)
This paper purposes to provide information on handling gifts-in-kind in Croatian public and academic libraries. It also recommends what should be done to improve practice with gifts for collections.The paper is based on the author’s research conducted using anonymous online questionnaire that was sent to Croatian public libraries (N=139) and academic libraries (N=73) in May 2011. After two weeks period, total number of 84 responses was received (40 public libraries and 44 academic libraries). In statistic analysis, some variables are tested by chi-square test to show whether differences between public and academic libraries are statistically significant. Majority of Croatian libraries do not have gift policy statements. Gifts do have a significant part in collection building, especially in Croatian academic libraries, but are not always handled in right way (i.e. according to IFLA’s guidelines). The paper shows quantity of gifts in the libraries, librarians’ reasons for not accepting some gifts, librarians’ methods in dealing with gifts, their way of communicating with donors or potential donors. This paper gives results of the first complete study of gift policies in Croatian public and academic libraries. As conclusion, a need for written gift policy in Croatian libraries is emphasized and some recommendations are given.
ENG